PELATIHAN PENULISAN NASKAH DINAS DI KECAMATAN ANGGANA, KUTAI KARTANEGARA: Business Correspondence Training in Anggana Subdistrict, Kutai Kartanegara - Yusriansyah, Eka; Kuncara, Singgih Daru; Mubarok, Ahmad; Sudirman, Eka Pratiwi (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2022)
Regarding correspondence, village administration must follow the recent regulation of official script for government administration, including Kutai Kartanegara regency. Regent regulation No 14 of 2018 about official script is no longer applicable and does not provide correct form of Indonesian spelling and grammar. The purpose of this community service is to create an effective administration and uniformity of official letters in Kutai Kartanegara. The method used is lecture and experiment. The implementation of this workshop is in line with the objective of the activity.